In vitro study of polygonum minus extract effect on skin cells healing capacity - Elnehrawy, Naema Yousri Fatthallah (2015)
Non-healing chronic wounds represent a common irritating health problem especially to diabetic patients and those with vascular insufficiency. Untreated chronic wounds may lead to serious complications like severe persistent pain, septicaemia or amputations. With the increasing ratios of aging population, obesity and the high prevalence of diabetic ulcers, chronic wounds are reflected as a considerable burden to the community and healthcare professionals. Polygonum minus (P. minus) leaves or “Kesum” as commonly known in Malaysia was found to have anti-oxidant properties, rich in some essential vitamins and minerals and have anti-ulcer and antimicrobial effects. In vitro study was carried out to determine the efficacy of different extracts of P. minus leaves on wound healing. Aqueous, ethanol and diethyl ether extracts of P. minus were obtained under reduced pressure in a rotary vacuum evaporator. Their total phenolic content and radical scavenging activity were evaluated by using Folin-Ciocalteu and DPPH (2, 2-diphenyl-1-picrylhydrazyl) assays, respectively. MTT assay was used to determine the cytotoxicity of the different extract solvents on human skin fibroblast cells (HSF1184). The enhancing capacity of P. minus extracts on cellular migration at their maximum and minimum non-toxic doses was evaluated using Scratch assay. Both aqueous (31µg/ml) and ethanol extract (63µg/ml) of P. minus leaves enhanced cellular migration and wound closure by 71% and 65% in day 1 respectively, comparing to 42% closure with the control. The induced scratch was completely healed in day 2 with aqueous and ethanol extracts while the control scratch healed by 79%. Moreover, aqueous extract exhibited the highest total phenolic content (217.1 mg GAE/l) and the highest antioxidant ability (IC50 = 56 µg/ml). Therefore, aqueous extract of P. minus leaves may play a role in improving the healing capacity of skin cells and in the same time provide a safer, more natural and costly effective remediation. Further in vivo studies may be needed to ascertain its effectiveness.